Comparative Biomechanical Evaluation of Novel Screwless Retained Dental Implant Prosthesis: A 3D Finite Element Analysis - Ki-Sun Lee; Jaeyeol Kim; JaeHyung Lim; Jae-Jun Ryu (Journal of Functional Biomaterials)
This study aimed to comparatively evaluate the biomechanical behaviors of three types of dental implant restorations: a screw-and-cement-retained prosthetic system (SCRP); a cementless screw-retained prosthetic system (SRP); and a novel screwless hook-retained prosthetic system (HRP). Three-dimensional finite element analysis (FEA) was used to evaluate biomechanical behavior. A comparative study of three dental implant prostheses was performed under two loading conditions: a vertical load of 100 N and an oblique load of 100 N at an angle of 30°. Under both loading conditions, the maximum von Mises stress values in the dental implant using the HRP system were lower (21.33 MPa) than those of the SCRP system (32.91 MPa), and the stress distribution of the implant prosthetic components tended to be more favorable than that of the SCRP system. Thus, the results show that the performance of the HRP system was comparable to that of a conventional SRP system under the same conditions. Regarding stress distribution, the novel screwless HRP system presents a viable alternative implant prosthodontic system to the conventional SCRP system.